Targeted CD7 CAR T-cells for treatment of T-Lymphocyte leukemia and lymphoma and acute myeloid leukemia: recent advances - Liu, Jile; Zhang, Yi; Guo, Ruiting; Zhao, Yifan; Sun, Rui; Guo, Shujing; Lu, Wenyi; Zhao, Mingfeng (Frontiers in Immunology, 2023)
The high expression of CD7 targets in T-cell acute lymphoblastic leukemia (T-ALL) and T-lymphoma has attracted considerable attention from researchers. However, because CD7 chimeric antigen receptor (CAR) T-cells undergo fratricide, CD7 CAR T-cells develop an exhaustion phenotype that impairs the effect of CAR T-cells. There have been significant breakthroughs in CD7-targeted CAR T-cell therapy in the past few years. The advent of gene editing, protein blockers, and other approaches has effectively overcome the adverse effects of conventional methods of CD7 CAR T-cells fratricide methods. This review, in conjunction with recent advances in the 64th annual meeting of the American Society of Hematology, provides a summary of the meaningful achievements in CD7 CAR T-cell generations and clinical trials over the last few years.